Jezus z Nazaretu Benedykta XVI a współczesna biblistyka - Rajmund Pietkiewicz (Wrocławski Przegląd Teologiczny)
Jesus of Nazareth is not only the result of the spiritual path of the Pope’s personal discovery of the figure of Jesus of Nazareth, but also his reaction to attempts at reaching out to historical Jesus, which led to the deepening of the gap between “historical Jesus” and “Christ of faith”. While reading the work, a question concerning its meaning for contemporary biblical studies emerges. Benedict XVI unmasks the non-academic character of some of the theses proposed by contemporary exegesis. He is of the opinion that an exegetic Catholic should apply so-called hermeneutic of faith, which constitutes a link between historical-critical studies of the Bible with its theological analysis. Jesus of Nazareth constitutes an example of the application of a hermeneutic of faith. The Pope recommends a critical approach to the findings of biblical studies.